PENGARUH KEPEMILIKAN NPWP, PEMERIKSAAN, PENAGIHAN, KESADARAN WP TERHADAP PENERIMAAN PAJAK BADAN DI KPP PRATAMA GIANYAR - W.P.P, Tjok Gde Agung Anggadhika; Jati, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.05.TAHUN 2019DO - 10.24843/EEB.2019.v08.i05.p01, 2019)
Purpose of this research is to find the effect of NPWP ownership, audit, collection and corporate taxpayer’s awareness to tax revenue in Gianyar KPP Pratama. Technique analysis used in this is multiple linear regressions. Before analysis process, Normality and Heterocedasticity Test were carried out using the SPSS program. The results of statistical analysis, showing the effect of NPWP ownership, audit, collection, and corporate taxpayers awareness with a significance level of t each of 0.039; 0,004; 0.046; 0,000. This means that the taxpayer's awareness bring positive and significant effect on tax revenue. For DJP which assigned to carry out taxation tasks, especially KPP Gianyar Pratama which has carried out its duties well so that in the future it will increase ownership of NPWP by conducting counseling taxpayers who have not registered and counseling to increase corporate taxpayer awareness. So that it can increase tax revenue, especially in KPP Pratama Gianyar